Antiatherogenic Effects of Quercetin in the THP-1 Macrophage Model In Vitro, With Insights Into Its Signaling Mechanisms Using In Silico Analysis - Huwait, Etimad A.; Saddeek, Salma Y.; Al-Massabi, Rehab F.; Almowallad, Sanaa J.; Pushparaj, Peter Natesan; Kalamegam, Gauthaman (Frontiers in Pharmacology, 2021)
Background: Atherosclerosis (AS), a major risk factor for stroke and brain tissue destruction, is an inflammatory disease of the blood vessels, and the underlying pathology is inflammation mediated by various chemokines and cytokines. Quercetin, a natural flavanol is reported to have both anti-inflammatory and anti-oxidant properties. As such, in the present study, we evaluated the anti-atherogenic effects of quercetin in a human THP-1 cell line in vitro, and also the signalling mechanisms using in silico analysis. Materials and Methods: THP-1 macrophages exposed to different concentrations of quercetin (5–100 M for 24 h) were tested for cytotoxicity. Real-time gene expression assay for intercellular adhesion molecule-1 (ICAM-1) and monocyte chemoattractant protein- 1 (MCP-1) was carried out following treatment with quercetin at 15 and 30 M for 24 h either in the absence or presence of interferon (IFN-γ) for 3 h to induce inflammation. Monocyte migration and cholesterol efflux were also assessed. Results: Quercetin did not exert any cytotoxic effects on THP-1 cells at the various concentrations tested. The gene expression assay showed a significant decrease in ICAM-1 (by 3.05, 2.70) and MCP-1 (by 22.71, 27.03), respectively. Quercetin at 15 μM decreased THP-1 monocyte migration by 33% compared to the MCP-1 treated cells. It also increased cholesterol efflux significantly by1.64-fold and 1.60-fold either alone or in combination with IFN- 𝛾, respectively. IPA of the molecular interactions of quercetin identified canonical pathways directly related to lipid uptake and cholesterol efflux. Furthermore, CD36, SR-A, and LXR-α also demonstrated significant increases by 72.16, 149.10, and 29.68 folds, respectively. Conclusion: Our results from both in-vitro and in-silico studies identified that quercetin inhibited the THP-1 monocyte migration, MCP-1, ICAM-1 and increased cholesterol efflux probably mediated via the LXR/RXR signalling pathway. Therefore, quercetin will help prevent cell infiltration in atherosclerotic plaques and reduce the risk of stroke or brain destruction.